Clinical profile of the patient with severe covid-19 in a northeastern hospital in México - Pérez Cruz, Itxel Del Carmen; Martínez Hernández, Ramon Alejandro; González Pérez, Ricardo; Maldonado Mancillas, Jesús Adrián Maldonado Mancillas (Horizonte Sanitario, 2025)
Objective: To determine the type of clinical profile and the association of severity of patients who developed severe COVID-19. Materials and methods: In the general hospital of the city of Heroica, Matamoros, in the State of Tamaulipas of the United Mexican States; A collection of clinical records will be carried out to see which patients previously had medication and influenced mortality in patients with COVID 19. Through a retrospective, observational and cross-sectional study using the statistical analysis technique; using the SPSS 32 program for information processing. Taking into account the criteria for inclusion, exclusion and definitive elimination. Results: At the Matamoros General Hospital; of 478 who suffered from severe COVID 19. A total of 161 patients were discharged due to clinical improvement compared to 317 who were taking some medication due to chronic degenerative. Of the 96 patients who did not consume medications, it was observed that 34 (6.9%) were discharged due to improvement against 63 (13.17%) who died despite not consuming medications. The combination of diabetes mellitus and hypertension resulted in 124 (25.94%) patients and 36 (7.53%) improved, against 88 (18.41%) deaths. Conclusions: Based on the present work, we found that polypharmacy (3 or more medications), together with comorbidities; may affect the concomitant administration of the baseline treatment of COVID-19 disease and have an unfavorable outcome. In this study, he also recorded a similar percentage of deaths of patients with two or more diseases, compared to healthy patients. Keywords: Profile; Polypharmacy; Comorbidity; Age; COVID 19.